Ultrafast Dynamics of Optical Nonlinearities in β-Ga2O3 - Sun, Yingfei; Fang, Yu; Li, Zhongguo; Yang, Junyi; Wu, Xingzhi; Jia, Jidong; Liu, Kun; Chen, Lu; Song, Yinglin (Frontiers in Materials, 2021)
We report the different nonlinear optical mechanisms and defect-related carrier dynamics in Sn-doped β-Ga2O3 crystal by utilizing time-resolved pump-probe technique based on phase object under UV excitation. The obtained nonlinear optical parameters arise from bound electron can be well explained by the theoretical calculation of two-band model and Kramers-Kronig transformation. By tuning the probe wavelength, the carrier nonlinearity can be modulated greatly due to additional absorption of defects within the bandgap. The results reveal that by choosing a proper probe wavelength that matches the defect state to the valence band, the nonlinear absorption and refraction of the carriers can be greatly enhanced, which provides an important reference for the design of gallium oxide-based waveguide materials and all-optical switching materials in the future.